Epigenetic Age Acceleration Reflects Long-Term Cardiovascular Health. Issue 8 (25th August 2021) - Joyce, Brian T.; Gao, Tao; Zheng, Yinan; Ma, Jiantao; Hwang, Shih-Jen; Liu, Lei; Nannini, Drew; Horvath, Steve; Lu, Ake T.; Bai Allen, Norrina; Jacobs, David R.; Gross, Myron; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Rationale: Epigenetic aging is a novel measure of biological age, reflecting exposures and disease risks independent of chronological age. It may serve as a useful biomarker of cardiovascular health (CVH) or cardiovascular disease risk for early detection or prevention. Objective: To examine associations between GrimAge acceleration (GrimAA), a measure of epigenetic aging calculated from the residuals of GrimAge regressed on chronological age, and 2 repeated CVH measures: a full score for the AHA Life's Simple 7 (diet, smoking, physical activity, body mass index, blood pressure, total cholesterol, and glucose) and a clinical CVH score (body mass index, blood pressure, cholesterol, and glucose). Methods and Results: We used Illumina array DNA methylation data from 2 prospective cohort studies, the CARDIA study (Coronary Artery Risk Development in Young Adults) and FHS (Framingham Heart Study), to calculate GrimAA and model associations with CVH. CARDIA randomly selected 1118 participants for assays at Y15 (2000–2001; mean age, 40 years) and Y20 (2005–2006); in FHS, 2106 Offspring participants had DNA methylation measured at exam 8 (2005–2008; mean age, 66 years). We examined multiple cross-sectional and longitudinal models of GrimAA and each CVH score measured at CARDIA Y0 to Y20 and FHS exams 7 to 8. In CARDIA, clinical CVH score from Y0 to Y20 was associated with Y15 and Y20 GrimAA (β range, −0.41 to −0.21 years per 1-point increase in CVH; P range, <0.01–0.01), as was full score (β range, −0.65 to −0.67 years; P <0.01 for all). These findings were validated in FHS (clinical score β range, −0.51 to −0.54 years; full score β range, −0.76 to −0.83 years; P <0.01 for all). Conclusions: Our data demonstrate that faster GrimAA is associated with the loss of CVH from young age. Epigenetic age may be a useful biomarker of cardiovascular disease risk and provides biological insight into the role of epigenetic mechanisms linking age-related CVH loss and cardiovascular disease.